Astronaut rotational motion during simulated microgravity - Stirling, L.; Newman, D.; Willcox, K. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
In order to reduce astronaut adaptation time and provide a safety countermeasure during extravehicular activity (EVA), this research effort investigates astronaut reorientation. Even though astronauts undergo hundreds of hours of training, the strategies for locomotion and orientation in a reduced gravity environment are not specifically prescribed. The problem of self-rotation, which is a human-body rotation without external torques, has been previously studied to determine its feasibility (Kulwicki et al., 1962; Scher and Kane, 1969; Parin and Gazenko, 1975). Since astronauts are not familiar with reorienting without external forces, they are unlikely to develop self-rotation techniques naturally. The goal of the current study was to experimentally examine the effects of rotation training. Understanding self-rotation will help develop an astronaut motion-training program and could contribute to safety countermeasures during EVA.